(untitled) (LEGAL DIALOGICA, 2025)
This study aims to analyze the criminal law aspects related to violence that leads to sexual harassment through the MiChat application in Makassar City. The background of this research is the widespread misuse of the MiChat application as a means of online prostitution, which is often accompanied by acts of violence. The research questions are how the criminal aspects applicable in Indonesia can be applied to perpetrators of violence and sexual harassment through the MiChat application, and what factors can aggravate or mitigate the perpetrator’s punishment. The research method used was an empirical legal method, with data collection techniques including direct interviews with police officers and review of relevant legal documents. The data obtained was then analyzed descriptively and qualitatively to obtain a comprehensive picture of the implementation of law enforcement in the field. This research shows that perpetrators of violence and sexual harassment through the MiChat app can be charged under various articles in the TPKS Law, the Criminal Code, the ITE Law, and the Pornography Law. However, law enforcement still faces obstacles in obtaining evidence and monitoring closed digital platforms. Factors that can aggravate the sentence include the level of violence used, the physical and psychological harm to the victim, and whether the victim is a minor. Meanwhile, factors that can mitigate the sentence include the perpetrator’s admission of guilt, remorse, and cooperation during the investigation. This study recommends strengthening regulations, increasing digital oversight, protecting victims, and providing digital education to the public to prevent sexual harassment on social media. Furthermore, law enforcement officials are expected to pay greater attention to the victims’ circumstances and the long-term impacts of digital-based sexual violence when determining punishments. Abstrak: Penelitian ini bertujuan untuk menganalisis aspek hukum pidana terkait kekerasan yang berujung pada pelecehan seksual melalui aplikasi MiChat di Kota Makassar. Latar belakang penelitian ini adalah maraknya penyalahgunaan aplikasi MiChat sebagai sarana prostitusi online yang seringkali disertai dengan tindak kekerasan. Rumusan masalah yang diajukan adalah bagaimana aspek pidana yang berlaku di Indonesia dapat diterapkan terhadap pelaku kekerasan dan pelecehan seksual melalui aplikasi MiChat, serta faktor-faktor apa saja yang dapat memberatkan atau meringankan hukuman bagi pelaku. Metode penelitian yang digunakan adalah metode hukum empiris, dengan teknik pengumpulan data melalui wawancara langsung kepada aparat kepolisian dan kajian dokumen hukum yang relevan. Data yang diperoleh kemudian dianalisis secara deskriptif kualitatif guna memperoleh gambaran menyeluruh mengenai implementasi penegakan hukum di lapangan. Hasil ini penelitian menunjukkan bahwa pelaku kekerasan dan pelecehan seksual melalui aplikasi MiChat dapat dijerat dengan berbagai pasal dalam UU TPKS, KUHP, UU ITE, dan UU Pornografi. Namun, penegakan hukum masih menghadapi kendala dalam pembuktian dan pengawasan platform digital tertutup. Faktor-faktor yang dapat memberatkan hukuman antara lain adalah tingkat kekerasan yang digunakan, kerugian fisik dan psikologis korban, serta jika korban masih di bawah umur. Sementara itu, faktor yang dapat meringankan hukuman mencakup pengakuan bersalah dari pelaku, adanya penyesalan, dan kerja sama dalam proses penyidikan. Rekomendasi penelitian ini adalah perlunya penguatan regulasi, peningkatan pengawasan digital, perlindungan terhadap korban, serta edukasi digital kepada masyarakat untuk mencegah pelecehan seksual di media sosial. Selain itu, aparat penegak hukum diharapkan lebih memperhatikan kondisi korban serta dampak jangka panjang yang ditimbulkan dari kekerasan seksual berbasis digital dalam menetapkan hukuman.